Pengembangan Sistem Informasi Perpustakaan Berbasis Web Untuk Efisiensi Pengelolaan Buku dan Anggota SMAN Colomadu - Lutfi Kamaludin; Jan Wantoro (Educatio, 2025)
Manual library management still faces various obstacles, especially related to the effectiveness and accuracy of recording book and membership data. This study aim to design and develop a web based library information system at SMAN Colomadu to improve operational efficiency and encourage students' interest in reading through the application of gamification elements. The system development follows the Agile method within System Development Life Cycle (SDLC) framework consisting of five stages: needs analysis, design, development, testing, and implementation. The system is built using the Laravel framework with the Model View Controller (MVC) approach. The evaluation was carried out through the black box testing method on ten users and showed that all features functioned optimally with a 100% success rate. Gamification elements such as awarding points and book review quizzes have been shown to increase student participation in literacy activities. Based on these results, the system is considered feasible to be implemented and contributes to the digital transformation of school library services.